A handheld DSP based vibration analyzer - Ginsberg, Samuel Isaac (Department of Electrical Engineering, 2014)
This dissertation investigates the design and implementation of a hand held vibration analyzer for use on electrical rotating machinery. The analyzer gathers data from an accelerometer and can present either acceleration, velocity or displacement information. Any information can be presented to the user in either the time or frequency domain. Numerical measurements can be made on the readings and readings can be stored onto a CompactFlash memory card. The instrument features its own type of file system and data storage metaformats. Facilities exist for the instrument to upload data to a computer or to download information from a computer. The instruments is made ergonomic by means of an extensive menu and hotkey system and by means of automated route tracking facilities.